(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
Photographs and drawings of a standing stone marked with unusual scratches were exhibited. Members who examined the photographs concluded that the marks were likely from farming tools impacting the stone, rather than deliberate markings.